2012
DOI: 10.1108/14502191211245561
|View full text |Cite
|
Sign up to set email alerts
|

Does country of brand origin (COBO) matter for the Lebanese consumers?

Abstract: PurposeThis study aims to examine country of origin (COO), price and brand effects on Lebanese consumers’ attitudes towards US products and brands while evaluating a low‐involvement product like chocolate.Design/methodology/approachThe research comprised formulation of a detailed questionnaire that was served to 488 administered at various shopping malls across Lebanon. Statistical analyses of data employed included Pearson correlation and analysis of variance (ANOVA) tests.FindingsThe data supported both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 63 publications
1
16
0
3
Order By: Relevance
“…Ha-Brookshire (2012) examined the hybrid effect of country of parts and country of manufacturing on consumer behaviour and product evaluation, and found that U.S. consumers consider cotton production or apparel manufacturing in the United States to be more sustainable than that in China. In addition, the evaluative criteria that consumers use to access the product quality are often impacted by the consumer's 'summary construct', or 'halo' effect associated with the country image (Ahmed et al, 2012;Han and Terpstra, 1988;Niss, 1996;Tigli et al, 2010).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…Ha-Brookshire (2012) examined the hybrid effect of country of parts and country of manufacturing on consumer behaviour and product evaluation, and found that U.S. consumers consider cotton production or apparel manufacturing in the United States to be more sustainable than that in China. In addition, the evaluative criteria that consumers use to access the product quality are often impacted by the consumer's 'summary construct', or 'halo' effect associated with the country image (Ahmed et al, 2012;Han and Terpstra, 1988;Niss, 1996;Tigli et al, 2010).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…It has been observed that the country of production has much more influence than the country of origin. This creates a close correlation between the brand and the country with which consumers associate it [62,64]. A 2007 study supports the idea that the COO has a strong influence in the decision-making process of chocolate consumers [62], especially for Germans, whose perception of chocolate quality increases if the country of origin is indicated [68].…”
Section: Country Of Originmentioning
confidence: 74%
“…No sustainability studies have been conducted in Asia or Oceania. Studies in Asia have been conducted in India [5,46,54,60,61], and one in Lebanon [64]. In Asia, the topics addressed were the influence of the country of origin, genetic modification, brand, demographic factors and product affection.…”
Section: Methodological Approaches and Research Issues Of Selected Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Without doubt, companies need to maintain good brands in market if they are to sustain market share and seek expansion; failing to do so results in brand switching to other more attractive brands. This important behavior has been studied widely in the literature to define the underlying factors to identify the right strategies to enhance or rebuild the brand (Ahmed et al, 2002;Ghosh et al, 2004;Zbib et al, 2010, Ahmed et al, 2012. The following sections describe the historical development of brand switching literature and explain how switching has varied significantly across different products and industries.…”
Section: Brand Usage From 2000 Onwardsmentioning
confidence: 99%